The Dynamics of Diplomacy - Leguey-Feilleux, Jean-Robert (New Dehli Viva Books, 2010)
This comprehensive new text offers a fresh, up-to-date look at the evolution, politics, and practice of diplomacy. How much of traditional diplomacy remains relevant today? How is the conduct of foreign relations changing?" "Leguey-Feilleux first provides a solid grounding in the history of traditional diplomacy, beginning with ancient times. He then reviews the forces of contemporary change - the dramatic developments in both international politics and the realm of technology that have affected the practice of diplomacy - and explores the full range of diplomatic modes." "Designed to be both authoritative and engaging, and with abundant in-depth case studies, The Dynamics of Diplomacy provides readers with a thorough understanding of all that contemporary diplomacy entails
Include Index, Bibliography and Accronyms.
Keywords: Diplomacy -- Diplomatie